PENGARUH BUDAYA ORGANISASI, KEMAMPUAN MANAJERIAL DAN DISIPLIN TERHADAP KINERJA - Nurasiah Nurasiah; Ade Jaya Sutisna; Yumhi Yumhi (E-Journal Studia Manajemen, 2020)
performance is influenced by organizational culture, managerial abilities and discipline. Using a causal study through a survey at the Rangkasbitung Branch of Bank Rakyat Indonesia (persero), Indonesia, for a sample of 37 employees, data for each variable were collected separately by respondents who filled out the questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is path analysis using correlation and regression.The results prove that there is an influence of organizational culture on performance, there is an influence of managerial ability on performance, there is an influence of discipline on performance, and there is an influence of organizational culture, managerial ability and discipline together on performance.These findings indicate that organizations need to consider the variables of organizational culture, managerial ability, and discipline in planning and human resource development at the Rangkasbitung Branch of Bank Rakyat Indonesia (Persero), Indonesia.